Rhamnogalacturonan from Acmella oleracea (L.) R.K. Jansen: gastroprotective and ulcer healing properties in rats. - Daniele Maria-Ferreira; Luisa Mota da Silva; Daniel Augusto Gasparin Bueno Mendes; Daniela de Almeida Cabrini; Adamara Machado Nascimento; Marcello Iacomini; Thales Ricardo Cipriani; Adair Roberto Soares Santos; Maria Fernanda de Paula Werner; Cristiane Hatsuko Baggio (PLoS ONE, 2014)
A rhamnogalacturonan (RGal) isolated from Acmella oleracea (L.) R.K. Jansen administered by oral route showed gastroprotective activity against acute lesions induced by ethanol. In this study, we investigated the gastric ulcer healing effect of RGal and its mechanisms of action. Intraperitoneal treatment of animals with RGal protected the gastric mucosa against acute lesions induced by ethanol, with participation of gastric mucus. Furthermore, in the chronic ulcer model, oral administration of RGal accelerates the gastric ulcer healing, accompanied by increasing of cellular proliferation and gastric mucus content, reducing inflammatory parameters and oxidative stress. In addition, the repeated 7 days-treatment of animals with RGal did not show alterations of clinical and behavioral symptoms, body and organs weights or plasmatic biochemical parameters. Collectively, these results showed that RGal has an interesting antiulcerogenic activity and could constitute an attractive molecule of interest for the development of new antiulcer agents.